Buried on Shine Mountain [videorecording (DVD)] - Butler, Stewart; Butler, Stewart; Brown, Kyle S.; Dalton, Gunnar; Butler, Nigel (Butler Media Productions LLC, 2025)
Two young farmhands eager for a life-changing fortune, join an experienced prospector on the treacherous journey up the haunted Shine Mountain. But the mountain holds more than just riches- it's dark secrets and dangerous past threaten to consume them all. As they push further into the wilderness, they'll have to face not only the elements but also the chilling forces that haunt the mountain.